Development of Low-Temperature Block Type Facility for Sea Water Desalination - Burdo O.G.; Terziev S.G.; Mordynskiy V.P.; Sirotyuk I.V.; Fateeva Ya.A.; Molchanov M.Yu. (Problems of the Regional Energetics, 2022)
This work is devoted to the fresh water deficit analysis. The importance of the research concern-ing water treatment is emphasized. A comparative analysis of water demineralization traditional methods is given and prospects for low-temperature desalination methods are shown. The in-crease in the world interest to the research of the block freezing innovative technologies was es-tablished, the priority in which belongs to the authors of this work. The aim of the work is to improve the block freezing devices during their transferring to a continuous operation mode. Achievement of this aim lies in a proposed universal design of the apparatus, in which the pro-cesses of crystallization, separation and melting of ice are sequentially implemented. A module for a continuous seawater desalination facility was developed. The energy and operational ad-vantages of the proposed method were described. The system modeling of this equipment was carried out. The target function of the modeling determined the key parameters of the process of the ice block gravitational separation — energy and salinity. It was proposed to correct the tradi-tional calculation principles for the outflow in channels by the “capillary drag” coefficient, which takes into account the relief surface of the ice capillaries. A technique for the engineering calculation of ice block salinity during separation was offered. The most significant result of the work lied in the fact of possibility to transfer the block freezing facilities to the continuous mode of sea water desalination with guaranteed salinity indicators. The significance of the work was that an energy-efficient freezing facility with ice recycling for the sea water demineralization in the flow was created.